Predictores de desempeño en docentes en la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana 2021 - Flores Torres, Jamil Ivan (2021)
The objective of the study was to determine if the organizational climate, leadership and job satisfaction are predictors of teaching performance in the Faculty of Education Sciences and Humanities of the National University of the Peruvian Amazon, 2021. The type of research was predictive with a field, transectional and multivariate design, the population consisted of 87 teachers from the different academic departments. The instruments were validated through the judgment of experts and the reliability for collecting data was verified using the internal consistency method. Information. The results show that 88.5% of teachers perceive teaching performance as good. In the bivariate analysis it was shown that the organizational climate (p = 0.0021 <0.05); leadership (p = 0.000 <0.05) and job satisfaction (p = 0.005 <0.05) presented a significant statistical association. This indicates that there is a relationship between teacher performance and predictors, concludes that, according to the binary logistic regression, the organizational climate (p = 0.048 <0.05), leadership (p = 0.005 <0.05) and satisfaction (p = 0.029 <0.05) predict teacher performance, showing a coefficient of determination of 24.2% to 47.5%.